Developing Interactive Digital Worksheets for Mathematics Learning - Kurniawati Sri Rianti Wahyuningsih; Heny Sri Astutik; Mukhlas Triono (Jurnal Inovasi Pendidikan Matematika (JIPM), 2026)
This study aims to determine the validity, practicality, and effectiveness of learning media developed in the form of Digital Student Worksheets (LKPD). This Research and Development (R&D) study was conducted to produce digital worksheets that can support and improve students’ mathematics learning. The development model employed in this study was ADDIE, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. The research subjects consisted of 27 junior high school students and one teacher, including 10 students in a small-scale trial and 17 students in a large-scale trial. The object of the study was the designed Digital LKPD. Data were collected through questionnaires, observations, and assessment tests. The data analysis techniques included: (1) product validity analysis, (2) product practicality analysis, and (3) product effectiveness analysis. The validation results from experts indicated that the developed Digital LKPD met the criteria of being highly valid. In addition, the results of student and teacher response questionnaires showed positive responses with percentages of 80% and 78%, respectively. The effectiveness test also demonstrated satisfactory student learning outcomes with an average percentage of 88.23%. Therefore, it can be concluded that the Digital LKPD developed for mathematics learning is valid, practical, and effective for use in the learning process.